(untitled) (Journal of the Bangladesh Agricultural University, 2026)
Although mango is a popular tropical fruit, it is climacteric and exhibits limited storage life due to a high respiration rate. Mangoes are also susceptible to particular storage pathogens at postharvest and thus possess a short shelf life. Mature Amrapali mangoes were treated with two concentrations of chitin nanofiber (CNF) - 0.1% CNF and 0.3% CNF, and two concentrations of chitosan, e.g., 0.1%, and 0.3% to evaluate their effects on the postharvest quality and shelf life. Disease-free and physiologically mature mangoes were collected from orchards. The experiments were designed using a Completely Randomized Design with three replications, and each replication consisted of 10 fruits. Fruits were evaluated for physical quality (weight loss, fruit firmness, and color changes), chemical attributes [changes in total soluble solids (TSS), titratable acidity (TA), vitamin C content], disease incidence, disease severity, and shelf life. Chitosan (0.1% and 0.3%) decreased the disease incidence and disease severity, retained more vitamin C, and increased the shelf life of mangoes. Although, CNF decreased weight loss of mangoes and kept the fruit firmer than the chitosan, it was less effective regarding chemical attributes including vitamin C and shelf life. Application of 0.3% chitosan significantly inhibited disease progression, lowering disease incidence and severity to 33.33% and 23.92%, respectively, while the untreated control showed 100% incidence and 99.33% severity. As both the chitosan concentrations (0.1% and 0.3%) had very similar effect, 0.1% chitosan can be recommended for postharvest mango preservation. More experiments should be conducted with different mango varieties and chitosan and CNF concentrations. J Bangladesh Agril Univ 24(1): 23–32, 2026